RANCANGAN MEDIA PEMBELAJARAN VIDEO TUTORIAL INTERAKTIF TARI KIPRAH LENGGER BERBASIS WEB LEARNING UNTUK KELOMPOK REMAJA SANGGAR BINA TARI BAYU KENCANA - Roosita Dewi Suriasih; Indar Sabri; Retnayu Prasetyanti Sekti; Anik Juwariyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the needs analysis and the design of an interactive video tutorial learning media for Tari Kiprah Lengger based on Web learning for adolescent groups at Sanggar Bina Tari Bayu Kencana, Probolinggo City. The study employed a Research and Development (R&D) approach using the ADDIE model, limited to the analysis and design stages. Data were collected through observation, questionnaires, interviews, and documentation. The research subjects consisted of dance instructors and 26 adolescent learners. The results of the analysis indicated that learners had a high interest in learning Tari Kiprah Lengger; however, they still experienced difficulties in memorizing movements, coordinating body movements, and synchronizing movements with musical rhythms. In addition, learners showed a strong desire for independent learning and required learning media that could be accessed flexibly and repeatedly. Based on the needs analysis, an interactive video tutorial learning media based on Web learning was designed using Canva and Articulate Storyline 3. The media integrates text, images, audio, video, interactive navigation, and learning control features to support independent learning activities. The materials presented include dance history, movement variations, video tutorials, music, makeup, and costumes. The findings indicate that the web learning-based instructional media design is relevant as an innovative alternative in learning Tari Kiprah Lengger and has the potential to improve learners’ motivation and dance skills.